2021
DOI: 10.1111/sode.12550
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Home Literacy Environment for children's linguistic and socioemotional competencies development in the early years

Abstract: Both linguistic and socioemotional competencies develop in early childhood in the context of children's learning environments at home and during interactions with their parents. To support linguistic competencies, the Home Literacy Environment (HLE) and shared reading routines play a crucial role. In turn, research also indicates associations between the HLE and children's socioemotional development. Based on a sam-This is an open access article under the terms of the Creative Commons Attribution-NonCommercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…Regarding income, parents provided their net income. For the analyses, the highest parental education, occupation, and family income were first z-standardized and then combined into an indicator of socioeconomic status (see Wirth et al, 2022 , for a similar approach).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding income, parents provided their net income. For the analyses, the highest parental education, occupation, and family income were first z-standardized and then combined into an indicator of socioeconomic status (see Wirth et al, 2022 , for a similar approach).…”
Section: Methodsmentioning
confidence: 99%
“…In a cross-sectional study, Wirth et al ( 2020 ) reported significant associations between families’ shared reading habits and socio-emotional skills of 3-year-old children. In a longitudinal study, Wirth et al ( 2022 ) documented relations between HLE (e.g., frequency of reading, onset of reading) and children’s socio-emotional skills via their language skills. In another longitudinal study, Rose et al ( 2018 ) found effects of HLE (e.g., frequency of shared book reading) at the age of three years on socio-emotional skills of 8-year-old children.…”
Section: Factors Influencing Early Socio-emotional Outcomesmentioning
confidence: 99%
See 3 more Smart Citations